1961
DOI: 10.1021/je00103a027
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Critical Region: Binary Systems with Chlorotrifluoromethane

Abstract: of phase equilibria is fundamental to the understanding of heterogeneous systems and to their use in separation processes and other chemical engineering operations. Phase equilibria in the critical region-the region a t elevated pressures above the critical temperature of one of the compounds-are characterized by large nonidealities in the gas phase as well as possible liquid phase nonidealities. These nonidealities are manifested in interesting but generally unpredictable phenomena such as the solution of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1966
1966
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…An example of very large negative partial molar volumes of a heavy solute in a supercritical fluid is shown in Figure 5 for the vinyl chloride-supercritical ethylene system (Ehrlich and Fariss, 1969). Other investigators have shown experimentally that the phenomenon of very large, negative partial-molar volumes exists for systems in which the solute is in dilute concentrations and the solvent is very close to its critical conditions (Eckert et al, 1983; Chappelear and Elgin, 1961;Ehrlich and Wu, 1973). Using a lattice-gas model, Wheeler (Wheeler, 1972) is able to theoretically explain this unusual partial molar volume behavior near the solvent critical point.…”
Section: Mole Fraction Vinylchlor Id Ementioning
confidence: 99%
“…An example of very large negative partial molar volumes of a heavy solute in a supercritical fluid is shown in Figure 5 for the vinyl chloride-supercritical ethylene system (Ehrlich and Fariss, 1969). Other investigators have shown experimentally that the phenomenon of very large, negative partial-molar volumes exists for systems in which the solute is in dilute concentrations and the solvent is very close to its critical conditions (Eckert et al, 1983; Chappelear and Elgin, 1961;Ehrlich and Wu, 1973). Using a lattice-gas model, Wheeler (Wheeler, 1972) is able to theoretically explain this unusual partial molar volume behavior near the solvent critical point.…”
Section: Mole Fraction Vinylchlor Id Ementioning
confidence: 99%
“…The parameter an is obtained from solubility data of the gas in pure solvent 1 such as that presented in Figure 6. Todd and Elgin (70) and Chappelear and Elgin (2) have reported such data for ethylene and chlorotrifluoromethane in organic liquids. For the 1-2 binary, *3 = 0 and Equation 21becomes…”
Section: Evaluation Of Margules Constantsmentioning
confidence: 91%
“…Effect of Margules Constants on Phase Behavior Since industrial separation processes operate in the Zi -Z2 region, it is important to determine how the Margules parameters affect the shape of the coexistence curve and the slope of the tie lines. In order for any liquid-liquid region to exist, at least one of the binary Margules constants must have a value greater than 2 (only positive values are being considered here); this is a consequence of the stability criteria given by Equation 5. Assume for illustrative purposes that the 2-3 binary satisfies this condition-that is,…”
Section: Evaluation Of Margules Constantsmentioning
confidence: 99%